2015
DOI: 10.1016/j.bmcl.2015.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a chondroitin sulfate disaccharide library and a GAG-binding protein interaction analysis

Abstract: Chondroitin sulfate (CS), which belongs to the glycosaminoglycan (GAG) superfamily, is a linear sulfated polysaccharide involved in various biological processes. CS structure is very heterogeneous and contains various sulfation patterns owing to the multiple and random enzymatic modifications that occur during its biosynthesis. The resultant microdomain structure in the CS chain interacts with specific biomolecules to regulate biological functions. Therefore, an analysis of the structure-activity relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Moreover, the interaction with FGF-2 requires the appropriate sequence of CS tetrasaccharides with such a mixed compositionthe location of the monosulfated disaccharide at the reducing end of such an oligo leads to the binding being voided [123]. On the other hand, both this study [123] and others [104,124,125] revealed a low affinity or a low binding capacity of the 4-O-sulfated disaccharide and the semi-synthetic CSs that contained this disaccharide for some ligands. This property may result from the high conformational rigidity of the 4-O-sulfated CS disaccharide.…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 69%
“…Moreover, the interaction with FGF-2 requires the appropriate sequence of CS tetrasaccharides with such a mixed compositionthe location of the monosulfated disaccharide at the reducing end of such an oligo leads to the binding being voided [123]. On the other hand, both this study [123] and others [104,124,125] revealed a low affinity or a low binding capacity of the 4-O-sulfated disaccharide and the semi-synthetic CSs that contained this disaccharide for some ligands. This property may result from the high conformational rigidity of the 4-O-sulfated CS disaccharide.…”
Section: Monosulfated Disaccharides Provide Interaction Surfaces For mentioning
confidence: 69%
“…Furthermore, the polymerization of the various disaccharides necessitates stereo-specific formation of a-glycosidic and b-glycosidic linkages. Considerable progress, however, has been made, both for HS [110][111][112][113][114][115] and for CS [116][117][118][119][120]. An emerging and powerful approach is the use of chemoenzymatic strategies [120], which are based on knowledge of HS biosynthesis [104] and HS biosynthetic enzymes [122][123][124].…”
Section: The Structures Recognized By Chemokinesmentioning
confidence: 99%
“…The KEGG pathway hsa00531 describes the glycosaminoglycan degradation biological process. This process is associated with drugs such as chondroitin sulfate, elosulfase alfa and nadroparin [6870]. Chondroitin sulfate reduces the fat in the blood stream [71, 72].…”
Section: Resultsmentioning
confidence: 99%